Hybridization of electrical resistance tomography to population balance model for accurate bubble column reactor hydrodynamic parameter predictions - Adetunji, Olubode Caleb (Department of Chemical Engineering, 2017)
A novel approach of obtaining bubble size and spatial distribution is developed by hybridising techniques of Electrical Resistance Tomography and the Gas Disengagement Technique using a Population Balance as a framework. As a result, detailed hydrodynamic predictions suitable for Bubble Column Reactor [BER] optimisation results with minimal computing effort. Electrical Resistance Tomography [ERT] is a technique for creating 3D images of objects occurring in space. The images are obtained through current stimulations through a body surface electrodes and measurements of resulting voltage signals due to interior spatial conductivity field distribution. The use of ERT imaging method for hydrodynamic parameter predictions in a BCR has a benefit of yielding high temporal resolution but low spatial resolution. The low spatial resolution in electrical imaging accounts for underestimated or overestimated hydrodynamic parameter predictions similar to results obtained from the use of alternative techniques. The population balance model [PBM] is a mathematical framework with which the spatial transport of properties of bubble population can be described. The PBM also allows for the description of the time-variant bubble population properties by a division of bubble population into size classes. Moreover, the PBM allows for the inclusion of models of bubble coalescence and breakage phenomena, which affect the distribution of bubble population properties during bubble swarming. The included source terms enable accurate modelling of the bubble evolution either in a steady or unsteady state fluid flow regime. The objective of the present study is to develop an ERT interpretation technique yielding a high accuracy reconstruction of bubble population distribution through coupling ERT measurements to a PBM. It is hypothesized that a higher accuracy interpretation of ERT measurements will result from coupling ERT measurements to a PBM. The ERT technique has the capacity to image the steady and time-dependent gas void fractions in column sections as bubbles swarm and during dynamic gas disengagement [DGD]. This ERT potential is explored in hybridizing ERT and a PBM in the present work.